(untitled) (Journal of Uzbekistan’s Development and Research, 2025)
This study presents a comparative analysis of the female detective fiction of Agatha Christie and Mary Roberts Rinehart. By examining their most notable characters Miss Marple and Nurse Hilda Adams the article explores cultural, gender, and narrative distinctions between British and American detective traditions. The research focuses on how both authors portray female intelligence, independence, and social roles through their sleuths. Through textual analysis of key novels, the paper highlights differences in suspense construction, setting, and moral tone. The findings reveal how national context and authorial perspective shape detective fiction in the early 20th century.